The uptake of tocopherols by RAW 264.7 macrophages - Gao, Rong (BioMed Central, 2002)
BACKGROUND: Alpha-Tocopherol and gamma-tocopherol are the two major forms of vitamin E in human plasma and the primary lipid soluble antioxidants. The dietary intake of gamma-tocopherol is generally higher than that of alpha-tocopherol. However, alpha-tocopherol plasma levels are about four fold higher than those of gamma-tocopherol. Among other factors, a preferential cellular uptake of gamma-tocopherol over alpha-tocopherol could contribute to the observed higher plasma alpha-tocopherol levels. In this investigation, we studied the uptake and depletion of both alpha-tocopherol and gamma-tocopherol (separately and together) in cultured RAW 264.7 macrophages. Similar studies were performed with alpha-tocopheryl quinone and gamma-tocopheryl quinone, which are oxidation products of tocopherols. RESULTS: RAW 264.7 macrophages showed a greater uptake of gamma-tocopherol compared to alpha-tocopherol (with uptake being defined as the net difference between tocopherol transported into the cells and loss due to catabolism and/or in vitro oxidation). Surprisingly, we also found that the presence of gamma-tocopherol promoted the cellular uptake of alpha-tocopherol. Mass balance considerations suggest that products other than quinone were formed during the incubation of tocopherols with macrophages. CONCLUSION: Our data suggests that gamma-tocopherol could play a significant role in modulating intracellular antioxidant defence mechanisms. Moreover, we found the presence of gamma-tocopherol dramatically influenced the cellular accumulation of alpha-tocopherol, i.e., gamma-tocopherol promoted the accumulation of alpha-tocopherol. If these results could be extrapolated to in vivo conditions they suggest that gamma-tocopherol is selectively taken up by cells and removed from plasma more rapidly than alpha-tocopherol. This could, in part, contribute to the selective maintenance of alpha-tocopherol in plasma compared to gamma-tocopherol.